PENANAMAN NILAI-NILAI NASIONALISME PADA GENERASI MUDA DI KEPULAUAN NATUNA - Susilowati, Endang; Respati Puguh, Dhanang; Naelili Masruroh, Noor (HUMANIKA, 2014)
Abstract This study aims to reveal the portrait of nationalism and explore the noble values and local wisdom of Natuna’s inhabitant that can strengthen the sense of nationalism. The method used in this article is historical method and ethnography. The result shows that the sense of nationalism of Natuna’s inhabitant who’s living in the outer islands is undoubtable, even though they are far away from the center of government, lack of attention, and therefore they are still left behind. In order to fortify their spirit of nationalism and their pride to the region and country, it is necessary to continuously instill national values ​​ to the younger generation in Natuna. Keywords: outer islands, sense of nationalism, noble values, local wisdoms